Two analyses of Indian foodgrain production and consumption data - "Sharma, J.S." (Washington, 1979)
Foodgrain production in India from 1961 to 1977 increased at an annual rate of 2.4 percent, barely keeping pace with the average population growth rate of 2.3 percent per year. The foodgrain situation during the three-year period 1975-77 was however, somewhat different. The three year average of 110.8 million metric tons produced was higher than what was achieved in the past in any single year or than any other three-year average. Stocks were at their highest level ever and real prices were declining. In spite of a comfortable food situation, per capita availability, or consumption, during the 1975-77 period was lower than during the 1970-72 or, even , 1960-62. Domestic production was enough to meet demand and all imports were used to build up stocks.
Keywords: Grain trade India